Effects of Antiviral Therapy on HBV Reactivation and Survival in Hepatocellular Carcinoma Patients Undergoing Hepatic Artery Infusion Chemotherapy - Liu, Shousheng; Lai, Jinfa; Lyu, Ning; Xie, Qiankun; Cao, Huijiao; Chen, Dabiao; He, Meng; Zhang, Bei; Zhao, Ming (Frontiers in Oncology, 2021)
Background This study aimed to investigate the influence of hepatic artery infusion chemotherapy (HAIC) on hepatitis B virus (HBV) reactivation in hepatitis B surface antigen (HBsAg) positive patients with primary hepatocellular carcinoma (HCC) as well as evaluate the role of antiviral prophylaxis in these patients. Methods We enrolled 170 HBsAg-positive advanced HCC patients receiving HAIC using mFOLFOX regimen, of which 137 patients received antiviral prophylaxis. Risk factors for HBV reactivation were analyzed. The overall survival (OS) from the first application of HAIC were compared between antiviral and non-antiviral groups. Results A total of 25 patients (14.7%) developed HBV reactivation after HAIC, of which 16 patients received antiviral treatment and nine patients did not. The incidence of HBV reactivation was 11.7% (16/137) in antiviral group and 27.3% (9/33) in non-antiviral group respectively. No antiviral prophylactic was the only significant risk factor for HBV reactivation (OR=12.35, 95% confidence interval (CI) 4.35–33.33, p<0.001). Patients in antiviral group received more cycles of HAIC compared with non-antiviral group (3.11 ± 1.69 vs 1.75 ± 1.18, p<0.05) at the time of HBV reactivated. Seven of the 25 HBV reactivation patients developed hepatitis. OS in antiviral group was significantly longer than that of non-antiviral group (median 16.46 vs 10.68 months; HR=0.57; 95% CI, 0.36–0.91; p<0.05). Conclusions HBV reactivation is more prone to occur in the HBsAg-positive HCC patients undergoing HAIC without antiviral prophylaxis. Regular monitoring of HBV DNA and antiviral prophylaxis are suggested to prevent HBV reactivation as well as prolong the OS of these patients. Name of the Trial Register HAIC Using Oxaliplatin Plus Fluorouracil/Leucovorin for Patients with Locally Advanced HCC. Clinical Trial Registration https://www.clinicaltrials.gov/, identifier NCT 02436044